Factors affecting stock market performance in Malaysia (2008 – 2018) / Mohamad Faizul Afham Ibrahim - Ibrahim, Mohamad Faizul Afham (Faculty of Business and Management, 2020)
The main of objective of this study to investigate the relationship between macroeconomic variables which consist of Crude Oil Price, Exchange Rate, Money Supply, Gross Domestic Product and Inflation towards the stock market performance in Malaysia. The study employed Multiple Linear Regression in order to find the relationships among independent variables and dependent variable. The data is collected from year 2008 until 2018 and it is conduct in yearly basis which is 10 years observations. From the result, it reveals that Money Supply and Crude Oil Price has a significant positive relationship towards stock market performance. While Gross Domestic Product found insignificantly positive relationship towards stock market performance in Malaysia and Exchange Rate found insignificantly negative relationship between stock market performances in Malaysia. While Inflation found significant negative relationship between stock market performance in Malaysia. These results give additional understanding of the relationship between the macroeconomic variables and Stock Market Performance plus it might also to be helpful for the speculator, regulator and investor.